On the Microstructural, Mechanical and Tribological Properties of Mo-Se-C Coatings and Their Potential for Friction Reduction against Rubber - Caessa, Jorge (2021)
Friction and wear contribute to high energetic losses that reduce the efficiency of mechanical systems. However, carbon alloyed transition metal dichalcogenide (TMD-C) coatings possess low friction coefficients in diverse environments and can self-adapt to various sliding conditions. Hence, in this investigation, a semi-industrial magnetron sputtering device, operated in direct current mode (DC), is utilized to deposit several molybdenum-selenium-carbon (Mo-Se-C) coatings with a carbon content up to 60 atomic % (at. %). Then, the carbon content influence on the final properties of the films is analysed using several structural, mechanical and tribological characterization techniques. With an increasing carbon content in the Mo-Se-C films, lower Se/Mo ratio, porosity and roughness appeared, while the hardness and compactness increased. Pin-on-disk (POD) experiments performed in humid air disclosed that the Mo-Se-C vs. nitrile butadiene rubber (NBR) friction is higher than Mo-Se-C vs. steel friction, and the coefficient of friction (CoF) is higher at 25 °C than at 200 °C, for both steel and NBR countersurfaces. In terms of wear, the Mo-Se-C coatings with 51 at. % C showed the lowest specific wear rates of all carbon content films when sliding against steel. The study shows the potential of TMD-based coatings for friction and wear reduction sliding against rubber.